The Broad Immunomodulatory Effects of IL-7 and Its Application In Vaccines - Huang, Juan; Long, Zhiyao; Jia, Renyong; Wang, Mingshu; Zhu, Dekang; Liu, Mafeng; Chen, Shun; Zhao, Xinxin; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; Tian, Bin; et al. (Frontiers in Immunology, 2021)
Interleukin-7 (IL-7) is produced by stromal cells, keratinocytes, and epithelial cells in host tissues or tumors and exerts a wide range of immune effects mediated by the IL-7 receptor (IL-7R). IL-7 is primarily involved in regulating the development of B cells, T cells, natural killer cells, and dendritic cells via the JAK-STAT, PI3K-Akt, and MAPK pathways. This cytokine participates in the early generation of lymphocyte subsets and maintain the survival of all lymphocyte subsets; in particular, IL-7 is essential for orchestrating the rearrangement of immunoglobulin genes and T-cell receptor genes in precursor B and T cells, respectively. In addition, IL-7 can aid the activation of immune cells in anti-virus and anti-tumor immunity and plays important roles in the restoration of immune function. These biological functions of IL-7 make it an important molecular adjuvant to improve vaccine efficacy as it can promote and extend systemic immune responses against pathogens by prolonging lymphocyte survival, enhancing effector cell activity, and increasing antigen-specific memory cell production. This review focuses on the biological function and mechanism of IL-7 and summarizes its contribution towards improved vaccine efficacy. We hope to provide a thorough overview of this cytokine and provide strategies for the development of future vaccines.